'Au milieu d'un tel et si piteux naufrage': the dynamics of shipwreck in Renaissance France - Oliver, J (2014)
This thesis examines the interweaving metaphorical and material aspects of shipwreck in Renaissance French writing. In a period marked by proliferating transatlantic and other exploration on the one hand, and, on the other, by religious civil wars, the ship was freighted with new political and religious, as well as poetic, significance. This rich symbolism reaches its height in the moments where ships—both real and symbolic—are threatened with disaster. The thesis demonstrates that shipwreck does not function merely as an emblem or poetic motif, but as a part, or the whole, of significant modes of narrative. Shipwreck in this period is rarely, if ever, recounted as a purely aesthetic embellishment: the ethics of spectatorship and of co-operation are of constant concern. I argue that the possibility of ethical distance from shipwreck—imagined through the Lucretian suave mari magno commonplace—is constantly undermined, not least through a sustained focus on the corporeal. Examining the ways in which the ship and the body are made analogous in Renaissance shipwreck writing, I show how bodies are allegorised in nautical terms, and, conversely, how ships themselves become animalised and humanised. Secondly, in many of the texts in my corpus it is shown or anticipated that the description, narration and dramatisation of shipwreck has an impact not only on the bodies of its victims, but on those of spectators, listeners, and readers, too. This insistence on the physicality of shipwreck is also reflected in the dynamic of bricolage that, I argue, informs the production of shipwreck texts in the Renaissance. The dramatic potential of both the disaster and the processes of rebuilding is exploited throughout the century, culminating, as I show, in a shipwreck tragedy. By the late Renaissance, shipwreck is not only the end of a story; it forms, more often than not, its beginning.